Metode Kitabah dan Kualitas Hafalan Al-Qur’an: Analisis Regresi pada Lembaga Tahfiz Madrasah Putri At-Taqwa Karanganyar - Afik Winda Khoirun Nisa; Vereza Kusumawardani; Asyro Mella Hanizah; Anisa Rahmawati; Dwi Putri Kristi Hermina; Oktavia Dina Astiari (WISE Pendidikan Indonesia, 2025)
This study is motivated by the phenomenon of declining Al-Qur'an memorization quality due to a lack of consistent and varied methods. The Kitabah (writing) method is proposed as a multisensory solution to enhance memory retention. This study aims to describe the implementation of the Kitabah method, measure the memorization quality of female students, and analyze the extent of the Kitabah method's influence on memorization quality at Madrasah Putri At-Taqwa Karanganyar. This research employs a quantitative ex post facto approach with a total sampling technique involving 33 female students. Data were collected through Likert-scale questionnaires and oral tests, then analyzed using simple linear regression. The results indicate that both the implementation of the Kitabah method and the students' memorization quality are in the